AMBIGUITAS GRAMATIKAL DALAM FILM THE INTERVIEW (2014) KARYA SETH ROGEN DAN EVAN GOLDBERG - Wondal, Marcella Tirsa; Pamantung, Rina P.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œGrammatical Ambiguity in The Interview (2014) movie by Seth Rogen and Evan Goldbergâ€. Ambiguity is a word, phrase, or statement which contains more than one meaning. The ambiguity that occurs at the sentence level is called grammatical ambiguity, this ambiguity is caused by the ambiguousness of grammatical forms or from the structure of sentence. The aims of this research are to identify and classify the forms of grammatical ambiguity and analyze the cause of the grammatical ambiguity that are found in The Interview movie (2014). The data source of this research is collected from The Interview Movie (2014). This research uses theory from Ullmann (1962). There are 62 dialogues of gramatical ambiguity. Those grammatical ambiguities are classified into 3 types; 1 preffix and suffix, inflectional ending, and equivocal phrasing (amphibology). There are, 42 prefix and suffix consisting of prefix un- totalling 6, prefix mis- totalling 3, prefix in- totalling 3, suffix â€“ly totalling 10, suffix â€“er totalling 6, suffix â€“ ed totalling 7, and suffix â€“s totalling 7. 13 Inflectional ending and 7 equivocal phrasing (amphibology).Keywords: Grammatical Ambiguity, The Interview Movie (2014), Semantic